Verification of the Factorial Structure the Scale of Professional Self-Concept in the Employees of Different Brazilian Companies - Formiga, Nilton Soares (2015)
The studies on the professional self-concept are increasingly expression and importance, since their understanding may contribute to the explanation of important variables within and outside the organizational context. In the present study, the objective was to investigate the factor structure of professional self-concept scale in employees of public and private Brazilian companies. 490 workers participated in the study, with 16-68 years, of which 169 belonged to public enterprises and 321 private companies. The results show that the original scale of three-factor model showed statistical indicators that justify the reliability and structural consistency. There was a confirmation of the proposed model by the authors of the scale, not only in the general sample of workers, but also separately in workers of public and private, and can therefore be observed that, in the three samples, the indicators were in agreement with the requirements in the statistical literature.